Penguatan Produktivitas dan Kualitas Produk Perikanan POKDAKAN Mina Perkasa Melalui Pendampingan Legalitas Usaha - Ikhsan Pratama; Muhammad Amir Biky; Meydy Fauziridwan (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance the productivity of gourami fish cultivation at POKDAKAN Mina Perkasa through the implementation of an integrated aquaculture system, strengthen consumer trust through the establishment of business legality for processed products, and expand market reach through the utilization of the POKDAKAN website. The program was implemented using a Participatory Action Research (PAR) approach oriented toward community empowerment and involved 17 members of the POKDAKAN. Program evaluation was conducted using a trend and change analysis and analyzed descriptively. The results indicate that POKDAKAN Mina Perkasa has successfully developed an official website and obtained business legality, thereby increasing consumer confidence in its processed products. This program generated direct and tangible impacts, including the adoption of technological innovations in the form of product legality and a group website, improved knowledge and skills in product marketing, and enhanced independence and sustainability of aquaculture-based enterprises.